2007
DOI: 10.2174/138161207780363040
|View full text |Cite
|
Sign up to set email alerts
|

Aquaretic Agents: Whats Beyond the Treatment of Hyponatremia?

Abstract: Unlike the more commonly used diuretics, aquaretic agents can induce an increase in urinary volume without incurring a loss of electrolytes. These molecules belong to a family of vasopressin receptor antagonists, V2 in particular, that regulate optional renal water re-absorption via the synthesis and expression of aquaporin-2. In view of their properties, they have become the agent of choice in the treatment of hyponatremic states with water retention, and different studies have demonstrated that they are more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 56 publications
(45 reference statements)
0
12
0
2
Order By: Relevance
“…Of these, V2 receptors are mainly found in the collecting tubules of kidney and are involved in free water reabsorption [20,21]. Aquaretics antagonize AVP effect by acting via V2 receptors and thereby retard the free water absorption [22]. Currently synthetic aquaretics such as tolvaptan, lixivaptan and conivaptan and natural aquaretics: Solidaginis virgaurea herba, Betulae folium, Ononidis radix, Graminis rhizoma are therapeutically used [19,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, V2 receptors are mainly found in the collecting tubules of kidney and are involved in free water reabsorption [20,21]. Aquaretics antagonize AVP effect by acting via V2 receptors and thereby retard the free water absorption [22]. Currently synthetic aquaretics such as tolvaptan, lixivaptan and conivaptan and natural aquaretics: Solidaginis virgaurea herba, Betulae folium, Ononidis radix, Graminis rhizoma are therapeutically used [19,22].…”
Section: Discussionmentioning
confidence: 99%
“…Aquaretics antagonize AVP effect by acting via V2 receptors and thereby retard the free water absorption [22]. Currently synthetic aquaretics such as tolvaptan, lixivaptan and conivaptan and natural aquaretics: Solidaginis virgaurea herba, Betulae folium, Ononidis radix, Graminis rhizoma are therapeutically used [19,22]. Interestingly, diuretics cannot be used as a treatment for hyponatreamia.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the effectiveness in the treatment of pathological conditions such as cirrhosis, SIADH and heart failure. 17 AVP is also involved in cellular proliferation of breast, pulmonary and pancreatic cancers. 18 Renal cancer may synthesize and express the V2-receptor, resulting in a proliferative effect in CAKI-2 and A498 cell lines.…”
Section: Disorders Of Hydroelectrolitic Balance During Neoplasiamentioning
confidence: 99%
“…En la misma década se inició la cuantificación rutinaria del sodio en el suero. La aproximación fisiopatológica fue que el aumento de la AVP plasmática se producía como consecuencia de un incremento de los estímulos no osmóticos presentes en gran parte de los cuadros de hiponatremia [10][11][12][13][14][15][16][17][18][19][20] . No fue hasta 20 años más tarde que se determinó dicha hormona por radioinmunoensayo, confirmándose, en efecto, que en la mayor parte de las situaciones de hiponatremia las concentraciones plasmáticas de AVP se hallaban elevadas o inadecuadas para la situación de hipoosmolalidad plasmática 10,11 .…”
Section: Desarrollo De Los Antagonistas Del Receptor De La Arginina-vunclassified